First record of mercury concentrations and stable isotopes (13C & 15N) in albacore (Thunnus alalunga) from the Western Equatorial Atlantic Ocean - Lacerda, Luiz Drude de (2024)
This paper reports the first record of total mercury (THg) concentrations in albacore (Thunnus alalunga), one of the main tuna species caught from the Western Equatorial Atlantic Ocean and presents a preliminary comparison with other regions and tuna species. Mean, standard deviation and range of concentrations in T. alalunga (515 ± 145 ng g− 1 ww; 294–930 ng g− 1 ww) with 92 % being of methyl-Hg, are higher than in albacore from other Atlantic Ocean subregions despite their smaller body size. These concentrations are similar to those from the Pacific and Indian oceans, but lower than in the Mediterranean. Compared to other sympatric tuna species, concentrations are higher than those in T. albacares and similar to T. obesus. These results are discussed considering the potential differences in stable isotope values ( 13C and 15N) of T. alalunga populations from multiple oceanic areas and compared to other tuna species worldwide.